Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Review: 67

Answer

$\dfrac{x}{x^{2}-36}+\dfrac{6}{x^{2}-36}=\dfrac{1}{x-6}$

Work Step by Step

$\dfrac{x}{x^{2}-36}+\dfrac{6}{x^{2}-36}$ Evaluate the sum: $\dfrac{x}{x^{2}-36}+\dfrac{6}{x^{2}-36}=\dfrac{x+6}{x^{2}-36}=...$ Factor the denominator and simplify: $...=\dfrac{x+6}{(x-6)(x+6)}=\dfrac{1}{x-6}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.